2001
DOI: 10.1074/jbc.m004164200
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Glycoprotein Ibα Binds to Thrombin Anion-binding Exosite II Inducing Allosteric Changes in the Activity of Thrombin

Abstract: The glycoprotein (GP) Ib-IX complex is a platelet surface receptor that binds thrombin as one of its ligands, although the biological significance of thrombin interaction remains unclear. In this study we have used several approaches to investigate the GPIb␣-thrombin interaction in more detail and to study its effect on the thrombin-induced elaboration of fibrin. We found that both glycocalicin and the aminoterminal fragment of GPIb␣ reduced the release of fibrinopeptide A from fibrinogen by about 50% by a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 64 publications
6
72
0
Order By: Relevance
“…Our findings confirm the role of exosite II (29)(30)(31)(32)(33)(34) and define that of exosite I (35), proving its necessary involvement in binding to immobilized but not soluble receptor. Although hirugen and HD1, exosite I ligands, lack inhibitory effect on FIIa interaction with GPIbα fragments linked to agarose (31) or plastic (30), we found that both inhibit binding to GPIbα fragments linked to immobilized antibodies and to membraneanchored platelet GPIb, the biologically relevant receptor.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings confirm the role of exosite II (29)(30)(31)(32)(33)(34) and define that of exosite I (35), proving its necessary involvement in binding to immobilized but not soluble receptor. Although hirugen and HD1, exosite I ligands, lack inhibitory effect on FIIa interaction with GPIbα fragments linked to agarose (31) or plastic (30), we found that both inhibit binding to GPIbα fragments linked to immobilized antibodies and to membraneanchored platelet GPIb, the biologically relevant receptor.…”
Section: Discussionsupporting
confidence: 85%
“…This confirms a role for electrostatic effects in ABE-II binding to GPIb␣, first suggested by its salt dependence (42). Whether binding to GPIb␣ allosterically modifies the structure of thrombin is still in question because conflicting results have been published indicating no effect on PAR1 peptide hydrolysis (42), but inhibitory effects on fibrinopeptide A release and D-Phe-ProArg-p-nitroanilide hydrolysis (43) and, more recently, FVIII activation (44).…”
Section: Figmentioning
confidence: 52%
“…Our current understanding of thrombin-mediated platelet activation is that its initial high-affinity binding to platelet surface GPIb-alpha is via exosite 2, which facilitates subsequent binding of a second thrombin molecule via exosite 1 (Li et al 2001;Celikel et al 2003;Dumas et al 2003). The interaction with GPIb-alpha also promotes thrombin binding to its proteolytically activated receptor-1 (PAR-1) via exosite 1, which leads to receptor cleavage .…”
Section: Discussionmentioning
confidence: 99%